A Normative Power Europe in the Caucasus? Human Rights in Georgia since the Rose Revolution - Canário, M.; Ferreira, D. S. (Europe as a Global Actor 2019, 2019)
The concept of Normative Power Europe (NPE), as developed by Ian Manners, conceives the Europe Union (EU) as an actor with an ideational nature, embodying common principles and shaping norm diffusion in the international system. In this work, we adapted Nathalie Tocci’s (2008) approach to the study of normative power based on three research questions: what does the EU want, how does it act, and what does it achieve. We will focus on human rights promotion, one of the EU founding principles and first mentioned in the 1973 Copenhagen declaration on European identity. In this research, we chose Georgia as a case study, a country with intentions of EU accession but part of the European Neighbourhood Policy (ENP), and dealing with human rights violations in the disputed territories of South Ossetia and Abkhazia. Our aims are to understand the EU’s objectives in the field of human rights in Georgia; how those objectives are manifested through processes of norm diffusion; and to examine potential results of EU involvement therein.